Counter-amores - Clarvoe, Jennifer (Phoenix poets., 2011)
Jennifer Clarvoe's second book, Counter-Amores, wrestles with and against love. The poems in the title series talk back to Ovid's Amores, and, in talking back, take charge, take delight, and take revenge. They suggest that we discover what we love by fighting, by bringing our angry, hungry, imperfect selves into the battle. Like a man who shouts for the echo back from a cliff, or the scientist who teaches her parrot to say, "I love you," or the philosopher who wonders what it is like to be a bat, or Temple Grandin's lucid imaginings of the last moments of cattle d